2017
DOI: 10.14302/issn.2576-6694.jbbs-17-1860
|View full text |Cite
|
Sign up to set email alerts
|

Benzoate Concentration and Cooperativity by a Substrate for Benzoate 1,2-dioxygenase from Benzoate-Degrading Rhodococcus Opacus 1CP

Abstract: We explored the effect of a change in substrate-benzoate (as sole carbon and energy source) concentration in growth medium on the activity of benzoate 1, 2-dioxygenase (BDO) of R.opacus 1CP cells, where BDO is the enzyme mediated the initial attack of benzoate. The activity of the enzyme was estimated by a change of respiration of whole freshly harvested bacterial cells (growth of the cells on benzoate) in response to injection of benzoate. It was shown that when concentration of growth substrate-benzoate decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…It consists of two different subunits. The sigmoidal dependency of V on S of benzoate and positive kinetic cooperativity by a substrate were observed for BDO of R. opacus 1CP cells [23]. It might be expected that the dependence of V on S for 3-CBA-1,2-DO of this culture would be sigmoidal.…”
Section: Resultsmentioning
confidence: 75%
“…It consists of two different subunits. The sigmoidal dependency of V on S of benzoate and positive kinetic cooperativity by a substrate were observed for BDO of R. opacus 1CP cells [23]. It might be expected that the dependence of V on S for 3-CBA-1,2-DO of this culture would be sigmoidal.…”
Section: Resultsmentioning
confidence: 75%
“…So, it was found that the concentration of the substrate, BA, in growth medium influenced the activity of BDO of Rhodococcus opacus 1CP. With increase of BA concentration, kinetics of the process catalyzed by BDO changes from the sigmoidal saturation Hill kinetics to the hyperbolic saturation Michaelis-Menten kinetics [35]. Using MMS, it was shown that induction led to classical Michaelis-Menten kinetics for the pair of Bacillus subtilis-fusaric acid [26].…”
Section: Induction Of Enzyme Systems Of Culture-receptor Cells Under ...mentioning
confidence: 99%
“…A sigmoid dependence of the rate of enzymatic reaction on substrate concentration for allosteric enzymes can be described using empirical formula suggested by Hill [5]: close proximity to the amount of active sites [4]. In [9] it was shown that depending on the conditions of cultivation of the cells containing benzoate dioxygenase (allosteric enzyme), the Hill coefficient varied from 1 to 3. This coefficient could not be used in order to go from constant S 0.5 of Hill equation to Michaelis constant, K m .…”
Section: = V Max •S/(k M + S)mentioning
confidence: 99%